1998
DOI: 10.7326/0003-4819-128-11-199806010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Human Rabies in the United States, 1980 to 1996

Abstract: In the United States, human rabies is rare but probably underdiagnosed. Rabies should be included in the differential diagnosis of any case of acute, rapidly progressing encephalitis, even if the patient does not recall being bitten by an animal. In addition to situations involving an animal bite, a scratch from an animal, or contact of mucous membranes with infectious saliva, postexposure prophylaxis should be considered if the history indicates that a bat was physically present, even if the person is unable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
158
2
9

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(172 citation statements)
references
References 11 publications
3
158
2
9
Order By: Relevance
“…Adherence to the WHO-recommended guidelines ensures protection against rabies 25 . Analyzing the cases of human rabies reported in the United States from 1980 to 1998, researchers at the Centers for Disease Control and Prevention observed that none of the 32 patients received post-exposure prophylaxis before the onset of clinical disease 16 . This highlights the importance of rapid post-exposure prophylaxis for individuals exposed to potential rabies virus transmitters.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to the WHO-recommended guidelines ensures protection against rabies 25 . Analyzing the cases of human rabies reported in the United States from 1980 to 1998, researchers at the Centers for Disease Control and Prevention observed that none of the 32 patients received post-exposure prophylaxis before the onset of clinical disease 16 . This highlights the importance of rapid post-exposure prophylaxis for individuals exposed to potential rabies virus transmitters.…”
Section: Discussionmentioning
confidence: 99%
“…Periodic increases in numbers of reported cases of rabies in states where the disease is enzootic among raccoons occur when populations of raccoons decimated by a previous epizootic again reach densities sufficient to support transmission of rabies virus. 9,10 The first field release of the V-RG vaccine in the United States began during 1990. 39 The vaccine was conditionally licensed in April 1995 and was fully licensed in April 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibody analysis and genetic sequencing indicated that 34 (91.9%) of these 37 persons were infected with bat rabies virus variants (14 of 15 [indigenously acquired; 4 received transplants from a rabies-infected donor]) since 2000 (Table 2). 6,9,10 Although infection of human beings with rabies virus from bats remains a rare occurrence, the prevention of such infection remains an important public health concern. 46 Rabies in bats is epidemiologically distinct from terrestrial rabies maintained by carnivores.…”
Section: 51mentioning
confidence: 99%
See 1 more Smart Citation
“…Entre 1981 y 1997 ocurrieron 20 casos de rabia en humanos transmitida por murciélagos no hematófagos en los Estados Unidos, lo que indica claramente su importancia como reservorios de la enfermedad (25).…”
unclassified